Atividade anti-bacteriana e anti- Trypanosoma cruzi de extratos de sementes de Lanchocarpus cultratus - Griebler, Aline (2017)
In the pharmaceutical area, plants and plant extracts are very important because they can serve as prototypes for the development of new drugs and as a source of pharmaceutical raw materials. Public health problems such as Chagas' disease and bacterial resistance to antimicrobials show a constant need for more efficient and safe drugs and active principles. In this context, the pharmacological study of plant species is extremely important. Among the plants with high medicinal potential, those of the genus Lonchocarpus stand out with several biological activities reported. The plant Lonchocarpus cultratus (Fabaceae) has proven action against sarcoma 180 and against Gram-positive bacteria. The main chemical constituents identified are cordoin, isocordoin, derricin and triterpenes. The objective of this study was to investigate the anti-bacterial action of the extracts of the seeds and roots from the L. cultratus species, to evaluate the anti-T.cruzi activity and the respective hemotoxicity of the extracts of the plant seeds and to carry out the chemical characterization of these extracts. The extracts hexane (LHS), dichloromethane (LDS) and methanolic (LMS) were obtained from plant seeds by successive macerations. The chemical characterization was performed by qualitative analytical methods and by 1H NMR. The anti-bacterial activity was evaluated by disc diffusion test, anti-T. Cruzi by direct counting method of the parasites in the Neubauer chamber and the hemotoxicity by UV method. Qualitative chemical tests showed that alkaloids, chalcones, coumarins, triterpenes and saponins are present in the roots and seeds of L. cultratus, flavonoids and steroids, only in the roots and tannins were not observed. Chalcones were identified by 1H NMR in LDS and LHS and steroids and terpenes in LMS. The LDS and LHS extracts showed activity against the epimastigote form of T. cruzi protozoan. The LDS results were better, showing inhibition of protozoan growth of 92.30% at the concentration of 175 μg.mL-1. The IC 50 value for this extract was 6.16 μg.mL-1 and at this concentration did not show toxicity to the red blood cells. The extracts studied did not present antimicrobial activity. The absence of anti-bacterial activity in the extracts of L. cultratus, especially in the root extract previously reported, suggests problems related to the stability or low concentration of bioactive chalcones in the extract. Although there is a need for additional research, anti-T. Cruzi and hemotoxicity obtained with the dichloromethane extract show an alternative potential for the treatment of Chagas' disease